2003
DOI: 10.1890/02-5309
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Early‐ and Late‐seral Mycorrhizae During Restoration in Seasonal Tropical Forest, Mexico

Abstract: Disturbance of vegetation and soil may change the species composition of arbuscular mycorrhizal fungi (AMF), which may in turn affect plant species responses to AMF. Seasonal tropical forest in Mexico is undergoing rapid conversion to early-successional forest because of increased wildfire and may require restoration. The responses of six early-and late-successional tree species were tested using early-and late-successional AMF inoculum. The plants were germinated in the shadehouse and received three inoculum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 76 publications
5
90
1
12
Order By: Relevance
“…Además, estas fuentes pueden ser utilizadas en el futuro para la producción de plántulas con fines de reforestación o plantaciones forestales comerciales en áreas deforestadas del trópico mexicano, lo que puede propiciar una pronta recuperación de estas áreas y, por ende, una mayor adaptación, tal y como lo sugiere Allen et al (2003) en sus resultados con algunas especies tropicales.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Además, estas fuentes pueden ser utilizadas en el futuro para la producción de plántulas con fines de reforestación o plantaciones forestales comerciales en áreas deforestadas del trópico mexicano, lo que puede propiciar una pronta recuperación de estas áreas y, por ende, una mayor adaptación, tal y como lo sugiere Allen et al (2003) en sus resultados con algunas especies tropicales.…”
Section: Discussionunclassified
“…El manejo de los HMA, integrado a la producción de plántula en vivero, es indispensable para asegurar el éxito de adaptación de las repoblaciones bajo condiciones naturales (Allen et al, 2003); por tal motivo, es importante integrar paquetes tecnológicos de diferentes especies forestales de importancia económica que se encuentran distribuidas en los tró-picos.…”
Section: Introductionunclassified
“…Studies on mycorrhizal plant dependency in rainforest have shown that most plant species are colonized by AMF (Zangaro et al, 2000;Kiers et al, 2000;Allen et al, 2003;Hernández & Salas, 2009). Poor nutrient availability in tropical soils constitutes an adequate environment for the development of AMF.…”
Section: Introductionmentioning
confidence: 99%
“…However, several authors agree on the advantages that the AMF inoculation provides on improving root growth, increasing plant survival, reducing the time plants spend in nursery, reducing cost production due to reduction of fertilizer applications, as well as increasing plant quality (Gehring & Connell, 2005;Allen et al, 2003;Hernández & Salas, 2009). Other advantages of AMF inoculation are related to the increase of photosynthetic rate during acclimatization and development of micro-propagated plants, the induction of drought resistance, and the protection of roots against pathogen attack (Ferrera-Cerrato & Alarcón, 2004;Gavito et al, 2008;Shukla et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The EOK analyses indicated that B. alicastrum root tissue contains a significant concentration of CaOx, which, when coupled with the Cairns et al (1997) root / shoot ratio (0.26) and Gill and Jackson (2000) root turnover rate (0.1 yr −1 ), predict that B. alicastrum deposits significant quantities of CaOx directly into its rhizosphere through the continuous decomposition and regeneration of root OM. Furthermore, investigations have demonstrated that B. alicastrum roots have strong associations with mycorrhizal fungi (Allen et al 2003;Allen et al 2005) that, Bravo et al (2013) (Table 2) even though the subjects are still very young (0.5-2 yrs). This was contrary to our hypothesis that the trees would be too young to have affected their local edaphic ecosystem; but, at the time of sampling, the Ma Rouge trees had already grown to 1.4-1.8 m in height and were producing significant quantities of CaOx, which was also detectable in the soils adjacent to them (5-25 g kg −1 ).…”
Section: Calcium Oxalate and B Alicastrummentioning
confidence: 99%